"Reverse tensor fascia latae perforator flap for reconstruction of knee defect: Anatomic study by computed tomographic angiography and a case report". Issue 6 (26th March 2022) - Boucher, Fabien; Abihannah, Michel; Chauvel‐Picard, Julie; Mojallal, Ali A.; Rouviere, Olivier; Brosset, Sophie
Abstract: Background: Reverse anterolateral thigh perforator (ALTp) pedicle flap can be used to reconstruct perigenicular defect thanks to the anastomoses between the descending branch of the lateral circumflex femoral artery (LCFA) and the perigenicular network. In a few cases, however, patients do not present any ALTp. We hypothesized that, in such cases, an adjacent perforator, the tensor fascia latae perforator (TFLp), emerging from the LCFA ascending branch, could be used instead. To assess the feasibility of this technique, a radiological study was conducted. A first patient was treated using this option. Methods: Sixty lower limb computed tomography were analyzed. The first treated patient was a 50‐years‐old man suffering from a 5‐mm chronic bone exposure and osteomyelitis. Other reconstructive options were not indicated since he presented a multiscarry leg, severe arteriopathy, and no ALTp. A TFLp flap was raised, and the LCFA ascending and descending branches were dissected in continuity. After ligation of the LCFA, the blood flow reversed in the descending branch to irrigate the flap through the ascending branch. Results: A TFL perforator was observed in all the cases of the radiological study. The LCFA branching pattern was compatible with achieving a reverse TFL perforator flap in 43 cases (72%). The average pedicle length was 32 cm (22–38 cm). In the first clinical case, the flap covered the defect easily. After three months, the patient showed no evidence of infection recurrence and recovered a painless walk. Conclusion: The reverse TFLp flap can be a suitable option for perigenicular reconstruction.